Accuracy and user performance evaluation of a blood glucose monitoring system which wirelessly transmits results to compatible insulin pumps: Evaluation of the CONTOUR PLUS LINK 2.4 blood glucose monitoring system, assessed according to ISO 15197:2013 criteria. (3rd May 2020) - Caswell, Michael; Brown, Daniel; Frank, Joy; Wallace, Jane F.; Pardo, Scott
Abstract: Objective: To perform evaluations of the CONTOUR PLUS LINK 2.4 blood glucose monitoring system (BGMS) assessed according to ISO 15197:2013 criteria. Methods: Clinical trial registered at ClinicalTrials.gov (NCT01824355). In a laboratory study (Study 1), capillary fingertip blood samples from 100 subjects were evaluated in duplicate, using three test strip lots. In a clinical trial (Study 2), 113 adults with diabetes were enrolled, and BGMS results and Yellow Springs Instruments (YSI) analyzer reference measurements were compared for subject- and trial staff-obtained fingertip blood and subject-obtained palm blood. Subjects completed a questionnaire to evaluate BGMS ease of use. Results: In Study 1, 100% of combined results (all test strip lots) fulfilled ISO 15197:2013 section 6.3 criteria. In Study 2, 97.7% of subject-obtained fingertip results and 100% of trial staff-obtained fingertip results met ISO 15197:2013 section 8 criteria. Additionally, 93.8% of palm results were within ± 15 mg/dL of mean YSI measurements for glucose concentrations <100 mg/dL or ± 15% for glucose concentrations ≥100 mg/dL. Most subjects found the BGMS easy to use. There were three non-serious, non-device related adverse events. Conclusion: The BGMS exceeded minimum ISO 15197:2013-specified accuracy criteria in the laboratory and in the hands of lay users with diabetes.